SEROPREVALENCIA DE Neospora caninum EN PERROS DE ESTABLOS LECHEROS DE LA CUENCA IZQUIERDA DEL VALLE DEL MANTARO - Cornejo P., Nathann (2004)
The neosporosis is an emergent disease, and considered as an important cause of abortion in cattle and a cause of neuromuscular disorders in dogs. The aim of the present study was to determine the seroprevalence of Neospora caninum in dogs of dairy farms in the left zone of the valley of Mantaro. A total of 24 serum samples of dogs living in and in the vicinity of 24 dairy farms of the provinces of Huancayo, Jauja and Concepcion were evaluated. The seroprevalence of antibodies against N. caninum was 19.4 ± 7.0% (24/124) in a dilution of 1:50, using the indirect immunofluorescense test. The percentage of farms having at least one infected dog was 62.5% (15/24). Statistical relationships between the rate of infection and the geographical location (province), age, sex, and origin (in and closeby the farm) did not exist. These results showed that dogs in the valley of Mantaro presented a moderate seroprevalence of N. caninum; and considering that the infection is present in most dairy farms of the valley, is recommended to limit the access of dogs to dairy farms in the valley.